A Hermeneutic Approach to the Translator’s Productive Bilingualism Model - Pastryk, Tetiana; Kykhtiuk, Oksana (East European Journal of Psycholinguistics, 2014)
This article describes the hermeneutic approach, which is used to study the model of сonсeptual productive bilingual translator activity. This allows examining and, by means of hermeneutic method, detecting features of translator that cause conative, cognitive-linguistic and personal strategies. The hermeneutic method is aimed at constructing the model of сonсeptual productive bilingual translator through the text as a product of his activity. The study of the text makes it possible to identify the peculiarities of business interpreter and efficiency of the basic translation strategies and personal, сonative and cognitive- linguistic. Application psyсhographology method and analysis of written text hermeneutic method of studying the original text and translation proves great potential method of textual interpretation. References Bochner, A. P. (1985). Perspectives on injury: representation, conversation and reflection. Handbook of Interpersonal Communication, 27–58. Dotsenko, E. L. (2004). Psiholohiya manipulyatsii: phenomeny, mehanizmy i zashchita [Psychology manipulation: phenomena, mechanisms and protection]. St.-Petersburg: Rech. Vygotskyi, L. S. (2001). Myshlenie i rech’[Thinking and speech]. Moscow: Labirint. Gladushina, R. M. (2004). Dosyagnennya smislovoii totozhnostі svіtospriymannya u perekladah virsha «If» R. Kiplinga ukraiinskou movou [Achieving semantic identity worldview in the translation of the poem «IF» R.Kiplinha Ukrainian language]. Philologichni Studii, 1, 23 – 29. Karpenko, Z. S. (2003). Ontopsyhologichni zasady konstruuivannya efektyvnogo etnokulturnogo naratyvu [Ontopsyhological principles of designing effective ethno-cultural narrative]. Psychologichni Perspektyvy, 4. 128–123. Karpenko, Z. S. (1997). Aksiopsychologiya osobystosti [Acsiopsychology of personlity].Kyiv: TOV Mizhnarodna Finansova Agentsiya. Leontyev, A. A. (2005). Osnovy Psiholingvistiki [Fundamentals of psycholinguistics].Moscow: Smysl. Lotman, Yu. (2004). Semiosfera [Semiosphere]. St. Peterburg: Iskystvo-SPb.,2004. Riker, P. (1995). Germenevtyka. Etyka. Politika. [Hermeneutics. Ethics. Politics]. Moscow: Academia. Riker, P. (1995). Konflikt interpreatsyi: Ocherki o germenevtike [The conflict of interpretations: Essays on hermeneutics]. Moscow: Medium. Chepeleva, N. V. (1999). Aktualnye problemy germenevtiki v kontekste psihoterapii [Apdating problems of hermeneutics in the context of psychotherapy]. Bulletin of Kharkiv State University, 439, 297–301.